(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تمت دراسة بعض خصائص الأمواج على شاطئ منطقة الأزهري، شمال مدينة اللاذقية، اعتماداً على معطيات محطة الأرصاد الجوية لسرعة الرياح ، الواقعة في المنطقة المذكورة، وتم إيجاد ارتفاع هذه الأمواج باستخدام جدولBeaufort . تم حساب ارتفاع الموجة المميز وبلغ حوالي ، وجذر متوسط مربعات الارتفاع Hrms=0.85 m ، والارتفاع المتوسط Hmean=0.61 m ، ومعدل أقصى عشر للأمواج وبلغ الارتفاع الأعظمي Hmax= 3.75 m . وقد وجد أن القيم المقاسة تتفق إلى حد ما مع القيم المحسوبة من العلاقات النظرية. علاوةً على ذلك تم حساب التوزع الاحتمالي لارتفاعات الأمواج, ووجد أن التوزع المناسب لها هو توزع Rayleigh الذي يصف التوزيع العشوائي للأمواج. The waves’ characteristics were considered at Al- Azharri Beach in the – north of Lattakia. They are based on the metrological station which are concerning wind speed and are situated in the late mentioned area. The wave heights were calculated by means of the famous Beaufort table. Statistical wave parameters show significant wave height Hs=H1/3 = 1.32 m, root average of the mean square wave height Hrms= 0.85 m , mean wave height Hmean = 0.61 m, highest one tenth H1/10= 1.91 m , and the maximum wave height Hmax = 3.75 m .It has been found that the measured values by us, are concerned with that calculated ones. In addition to that we calculated probability distribution of the heights of sea waves. The best distribution which describes our results, is Rayleigh, s one.